2019
DOI: 10.7717/peerj.7938
|View full text |Cite
|
Sign up to set email alerts
|

Tree age did not affect the leaf anatomical structure or ultrastructure of Platycladus orientalis L. (Cupressaceae)

Abstract: Tree aging is a new research area and has attracted research interest in recent years. Trees show extraordinary longevity; Platycladus orientalis L. (Cupressaceae) has a lifespan of thousands of years. Ancient trees are precious historical heritage and scientific research materials. However, tree aging and tree senescence have different definitions and are poorly understood. Since leaves are the most sensitive organ of a tree, we studied the structural response of leaves to tree age. Experiments investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…(Figures 1.E, 6.F). The obtained results in this study relating to the type and distribution of anatomical features (epiderm, hypoderm, vascular bundle) correspond to previous anatomical studies (Hamidpour et al, 2011;HU and YAO, 1981;Koçyiğit and Tümer, 2017;Yao and Hu, 1982;Zhou et al, 2019).…”
Section: Secretory Canal (Resin Duct)supporting
confidence: 91%
“…(Figures 1.E, 6.F). The obtained results in this study relating to the type and distribution of anatomical features (epiderm, hypoderm, vascular bundle) correspond to previous anatomical studies (Hamidpour et al, 2011;HU and YAO, 1981;Koçyiğit and Tümer, 2017;Yao and Hu, 1982;Zhou et al, 2019).…”
Section: Secretory Canal (Resin Duct)supporting
confidence: 91%
“…Their results demonstrated that the loss of old spruce trees will cause a decrease in genetic variability in the Norway spruce population within the exceptionally valuable Białowieża Primeval Forest. The ancient trees of P. orientalis growing in the middle reaches of the Yellow River are precious plant genetic resources as well as important symbols and products of thousands of years of history and culture in China [8]. Prior studies have noted the importance of habitat loss and fragmentation as two of the greatest threats to the loss of diversity of P. orientalis [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its long lifespan, beautiful trunk, sacred status and important economic value, P. orientalis has been planted in gardens, temples and the vicinity of mausoleums since ancient times [7]. It is the most widely planted cemetery tree species in China [8]. The age of P. orientalis can reach hundreds or even thousands of years [9].…”
Section: Introductionmentioning
confidence: 99%